Scleromyxoedema with features of systemic sclerosis. - Verma, U N (1992)
The case is described of a patient with scleromyxoedema with features typical of systemic sclerosis. The features were so characteristic that the disease was misdiagnosed as systemic sclerosis. A brief review of the association of the two diseases is given.